A critical literature review on violence against older women in Latin America and the Caribbean: has an intersectional research approach been achieved? - Ramos Bonilla, Gabriela (2021)
This article makes a critical and systematic review of 72 qualitative and quantitative studies related to the subject of violence against older women (VOW) in LAC between the years 2000 and 2020. It aims to evaluate to what extent they have managed to analyse this phenom- enon using an intersectional approach —as a gender— and age-based problem simultaneously and the gaps, limitations and main findings of this body of research. This review shows that this subject’s study has been dominated by the conceptual frameworks of «elder abuse» and «violence against women» (VAW). They approached this subject through a medical perspective and quantitative methodologies and failed to fully understand it since they addressed violence in a frag- mented way. In comparison, a novel group of studies carried out by social researchers through the conceptual framework of «intersectionality» approached violence from a life-course and phenomenological perspective. This research concludes that even though intersectional studies are still scarce in LAC, they show great potential to reveal the cumulative nature of violence, the interconnection between different lifetime experiences of abuse, to explore older women’s belief systems, their daily experiences of abuse, dilemmas, barriers and strategies for seeking help. This framework will allow the construction of theory inductively and grounded on contextualised evidence is a powerful weapon to confront former theoretical frameworks.